Analysis Of Cattle Livestock Development Potential In North Sumatra Province - Elvin Desi Martauli; Seringena Br Karo; Swati Sembiring; Riduan Sembiring (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
This study aims to identify the location of cattle development and study cattle in North Sumatra Province. The method in this study used purposive area sampling where the determination of the research area was taken based on the district/city having cattle from 2016-2020 at BPS North Sumatra. Data analysis was carried out using the Growth Ratio Model used in the analysis (MRP) and location quotient (LQ). The results showed that the districts included in classification I were Asahan, Dairi, Deli Serdang, South Tapanuli, Mandailing Natal, Labuhanbatu, Batu Bara, Tebing Tinggi, Toba, Karo, Simalungun, Serdang Bedagai, Langkat, South Labuhanbatu, North Labuhanbatu. , Tanjung Balai, Binjai, Medan, Pematang Siantar, North Padang Lawas, Padang Sidempuan, Central Tapanuli and Padang Lawas. For the classification area II, the districts of North Tapanuli, Nias, South Nias, North Nias, West Nias, Gunung Sitoli, Samosir, Sibolga, Humbang Hasundutan, Pakpak Bharat.